A CROSS-SECTIONAL SURVEY ON PSYCHOLOGICAL WELL-BEING AND EMOTIONAL INTELLIGENCE FACTORS AMONG COLLEGE STUDENTS - Dr. Jyoti Madhur; Dr. Anubhav Madhur (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
BACKGROUND: Most studies examining psychological well-being predominantly concentrate on academic contexts, emphasizing advancements in learning, concentration, and academic performance. Nonetheless, the influence of psychological well-being on stress and performance during the transition to college—an experience often fraught with challenges for both students and their families—has not been sufficiently investigated. Students frequently encounter pressures from parents, peers, and faculty, which can lead to mental disturbances such as anxiety and depression.OBJECTIVES: The primary objective of this study was to evaluate psychological well-being and emotional intelligence among college students.METHODS: The study recruited 237 students from XXX. Data collection was conducted using the Ryff Psychological Well-Being Scale and the Wong and Law Emotional Intelligence Scale (WLEIS).RESULTS: The analysis yielded a P value of 0.005, indicating a statistically significant relationship between psychological well-being and emotional intelligence. Notably, Female students demonstrated higher levels of psychological well-being, whereas male students exhibited greater emotional stability.CONCLUSION: This study underscores a correlation between various facets of psychological well-being and elevated emotional intelligence. Gender differences were identified, revealing that females displayed superior psychological well-being, while males showed enhanced emotional stability. In summary, a significant relationship between psychological well-being and emotional intelligence was affirmed.